IL-11 Is Elevated and Drives the Profibrotic Phenotype Transition of Orbital Fibroblasts in Thyroid-Associated Ophthalmopathy - Wu, Pengsen; Lin, Bingying; Huang, Siyu; Meng, Jie; Zhang, Fan; Zhou, Min; Hei, Xiangqing; Ke, Yu; Yang, Huasheng; Huang, Danping (Frontiers in Endocrinology, 2022)
Orbital fibrosis is a hallmark of tissue remodeling in thyroid-associated ophthalmopathy (TAO). Previous studies have shown that interleukin (IL)-11 plays a pivotal profibrotic role in various inflammatory and autoimmune diseases. However, the expression pattern of IL-11 in patients with TAO and whether IL-11 is mechanistically linked with pathological fibrosis remains unknown. In this study, we investigated IL-11 levels in the serum and orbital connective tissue of patients with TAO, and evaluated the correlation of these levels with the patient’s clinical activity score. We also evaluated the expression pattern of IL-11Rα in orbital connective tissue. Furthermore, we elucidated the regulatory factors, profibrotic function, and downstream signaling pathways for IL-11 in TAO using in vitro studies. IL-11 levels in serum and orbital connective tissues were increased in patients with TAO, as compared with healthy controls. In addition, both levels were positively correlated with disease activity. Single-cell RNA sequencing of orbital connective tissue indicated that IL-11Rα was dominantly expressed in orbital fibroblasts (OFs). RNA sequencing of paired unstimulated and transforming growth factor (TGF)-β1-stimulated samples demonstrated that upregulation of IL-11 expression defined the dominant transcriptional response. IL-11 signaling was also confirmed to be downstream of TGF-β1 and IL-1β. Therefore, we deduced that IL-11 protein is secreted in an autocrine loop in TAO. We also indicated that IL-11 mediated the profibrotic phenotype switch by inducing the expression of myofibroblast differentiation markers, including α-smooth muscle actin and collagen type I α1, which could be abrogated by an anti-IL-11 neutralizing antibody. Furthermore, we revealed that extracellular regulated protein kinase may be a crucial factor in the pro-fibrotic, translationally specific signaling activity of IL-11. These data demonstrate that IL-11 plays a crucial role in orbital fibroblast phenotype switching and may be a potential therapeutic target candidate for the treatment of TAO.